Influence of opponent standard on activity profile and fatigue development during preseasonal friendly soccer matches: a team study - Rago, V.; Silva, J.; Mohr, M.; Randers, M.; Barreira, D.; Krustrup, P.; Rebelo, A. (Research in Sports Medicine, 2018)
We examined the influence of competitive standard of the opponent on activity profile and fatigue during preseason friendly soccer matches. Time motion analysis was performed in a male professional soccer team (N = 14) during six friendly games played against professional, semi-professional and amateur-level opponents (PL, SPL and AL). The reference team covered higher acceleration distance, acceleration and deceleration > 2 m· s-2 distance against PL than AL (ES = 0.77 to 0.91). Acceleration and deceleration distance > 2 m· s-2 was also higher (ES = 0.66 to 0.84) against SPL than AL. Greater decreases in total distance, distance> 16 km· h-1 and > 22 km· h-1, total acceleration and deceleration, acceleration and deceleration distance > 2 m· s-2 (ES = 0.84 to 2.20) were also observed during PL compared to AL opponent. Playing against a stronger opponent seems to be more physically demanding, with special emphasis on events related with change of velocity (accelerations and decelerations). Declines in physical performance appear more evident against a higher opponent.